LANGUAGE AND CULTURE IN ENGLISH CLASSROOMS - Odiljonova Jumagul; Toshmatov Alimardon Sotvoldiyevich (Ta’lim innovatsiyasi va integratsiyasi, 2024)
This article explores the symbiotic relationship between language and culture within English classrooms, emphasizing the importance of fostering cultural awareness, celebrating linguistic diversity, and promoting intercultural communication skills. It advocates for the integration of multicultural perspectives and literature to enrich the learning experience and cultivate empathy and understanding among students from diverse backgrounds.